2018
DOI: 10.1111/1365-2478.12648
|View full text |Cite
|
Sign up to set email alerts
|

Review Paper: A semi‐empirical model of strain sensitivity for 4D seismic interpretation

Abstract: We reformulate the original model of Hatchell and Bourne and Røste, Stovas and Landrø that couples fractional velocity change to subsurface strain via a fundamental constant R. The new model combines elastic compressibility of a dual‐porosity system for a sand–shale mixture with horizontal planes of inter‐granular weakness. The majority of observed R‐factor magnitudes from post‐stack 4D seismic data in both the reservoir and overburden can thus be explained. R is predicted to depend strongly on lithology and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…In practice, an overburden extension-reservoir compression polarity reversal is not commonly observed at top reservoir or in the immediate underburden (Hatchell and Bourne 2005b). This observation supports the growing conclusion that R-factors in the overburden must be large -it is observed that they must be around 5 or greater (MacBeth et al 2018). Indeed recent work by Røste and Ke (2017) has suggested that overburden factors of up to 17 may be possible.…”
Section: Time-shifts Related To Reservoir Pore Pressure Changessupporting
confidence: 80%
See 4 more Smart Citations
“…In practice, an overburden extension-reservoir compression polarity reversal is not commonly observed at top reservoir or in the immediate underburden (Hatchell and Bourne 2005b). This observation supports the growing conclusion that R-factors in the overburden must be large -it is observed that they must be around 5 or greater (MacBeth et al 2018). Indeed recent work by Røste and Ke (2017) has suggested that overburden factors of up to 17 may be possible.…”
Section: Time-shifts Related To Reservoir Pore Pressure Changessupporting
confidence: 80%
“…This observation supports the growing conclusion that R‐factors in the overburden must be large – it is observed that they must be around 5 or greater (MacBeth et al . ). Indeed recent work by Røste and Ke () has suggested that overburden factors of up to 17 may be possible.…”
Section: The Magnitude Of 4d Seismic Time‐shiftsmentioning
confidence: 97%
See 3 more Smart Citations